Old Kuala Lumpur - Gullick, J. M. (Oxford University Press, 1994)
Kuala Lumpur, founded around 1860, has had an eventful history, twice occupied (in 1872 and again in 1942) by enemy forces, and inundated by floods as recently as 1926. Even more remarkable is the improbable rise of a small trading post on a river bank far in the interior, to the proud status of state, then federal, and finally national capital.